Prevalence and genetic analysis of triplicated α-globin gene in Ganzhou region using high-throughput sequencing - Xie, Xinxing; Gan, Jinhui; Liu, Zezhang; Zhou, Yulian; Yuan, Kun; Chen, Zhigang; Chen, Shiping; Zhou, Rui; Liu, Lipei; Huang, Xiaoyan; Zhang, Yan; Liu, Qian; et al. (Frontiers in Genetics, 2023)
α-globin gene triplication carriers were not anemic in general, while some studies found that α-globin gene triplication coinherited with heterozygous β-thalassemia may cause adverse clinical symptoms, which yet lacks sufficient evidence in large populations. In this study, we investigated the prevalence and distribution of α-globin gene triplication as well as the phenotypic characteristics of α-globin gene triplication coinherited with heterozygous β-thalassemia in Ganzhou city, southern China. During 2021-2022, a total of 73,967 random individuals who received routine health examinations before marriage were genotyped for globin gene mutations by high-throughput sequencing. Among them, 1,443 were α-globin gene triplication carriers, with a carrier rate of 1.95%. The most prevalent mutation was ααα anti3.7 /αα (43.10%), followed by ααα anti4.2 /αα (38.12%). 42 individuals had coinherited α-globin gene triplication and heterozygous β-thalassemia. However, they did not differ from the individuals with heterozygous β-thalassemia and normal α-globin (αα/αα) in terms of mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) levels. In addition, heterogenous clinical phenotypes were found in two individuals with the same genotype. Our study established a database of Ganzhou α-globin gene triplication and provided practical advice for the clinical diagnosis of αglobin gene triplication.